PEMBELAJARAN MENULIS TEKS BIOGRAFI DENGAN MENGGUNAKAN METODE THINK TALK WRITE BERBANTUAN MEDIA AUDIO VISUAL PADA SISWA X SMK SANGKURIANG 1 CIMAHI - Mutia, Revi Siti (IKIP Siliwangi, 2020)
This research is motivated by the difficulty of students in writing biographical texts in accordance with the structure and rules of language in writing biographical texts. This study aims (1) To determine the difficulties experienced by students in writing biographical texts using the think talk write method assisted by audio visual media, (2) Scenarios and implementation in learning to write biographical texts using the think talk write method assisted by audio-visual media, (3) To determine the response of teachers and students in learning. The method used in this research is descriptive qualitative. The assessment instrument in this study is a learning activity to write biographical texts which includes questionnaire sheets, observation sheets, and written tests in the form of questions of knowledge and skills. The results of this study indicate that learning to write biographical texts using the think talk write method is said to be